2017
DOI: 10.1186/s12864-017-3578-9
|View full text |Cite
|
Sign up to set email alerts
|

Screening and evaluating of long noncoding RNAs in the puberty of goats

Abstract: BackgroundLong noncoding RNAs (lncRNAs) are involved in regulating animal development, however, their function in the onset of puberty in goats remain largely unexplored. To identify the genes controlling the regulation of puberty in goats, we measured lncRNA and mRNA expression levels from the hypothalamus.ResultsWe applied RNA sequencing analysis to examine the hypothalamus of pubertal (case; n = 3) and prepubertal (control; n = 3) goats. Our results showed 2943 predicted lncRNAs, including 2012 differential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 57 publications
4
43
0
Order By: Relevance
“…To date, many studies have been performed to study ncRNAs (noncoding RNAs) of dairy goat mammary and have revealed a landscape of transcriptomics, miRomics, and proteomics [7][8][9]. However, to the best of our knowledge, studies of lncRNAomics of dairy goats have been reported only in ovary, hair follicle, skeletal muscle, hypothalamus, and skin pigmentation tissue [10][11][12][13][14][15][16], and there are no studies of the lncRNAomics of dairy goat mammary gland tissues in different lactating periods.…”
Section: Introductionmentioning
confidence: 99%
“…To date, many studies have been performed to study ncRNAs (noncoding RNAs) of dairy goat mammary and have revealed a landscape of transcriptomics, miRomics, and proteomics [7][8][9]. However, to the best of our knowledge, studies of lncRNAomics of dairy goats have been reported only in ovary, hair follicle, skeletal muscle, hypothalamus, and skin pigmentation tissue [10][11][12][13][14][15][16], and there are no studies of the lncRNAomics of dairy goat mammary gland tissues in different lactating periods.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is possible that DNA methylation affects the initiation of puberty via lncRNA. The lncRNAs which participated in regulation of puberty in goats were screened as our previous research (Gao et al, ). In this study, we detected different methylation expression levels of the lncRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptome assembly was done according to the description by Gao et al (2017). Briefly, we used the following GTF file (https:// www.ncbi.nlm.nih.gov/genome/?term=Capra_hircus) to annotate the goat genome.…”
Section: Transcriptome Assemblymentioning
confidence: 99%
See 2 more Smart Citations